2021
DOI: 10.1136/bcr-2020-238808
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic challenges in neoplastic meningitis presenting as intracranial hypertension

Abstract: A diagnosis of idiopathic intracranial hypertension should be considered only after careful exclusion of all possible aetiologies. We report a case of neoplastic meningitis presenting as intracranial hypertension with inconclusive repeated cerebrospinal fluid (CSF) cytology and MRI of brain, emphasising the importance of meticulous CSF analysis and role of early whole-body PET–CT scan for diagnosis of systemic malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several reports described spinal cord tumors misdiagnosed as IIH: In one, the patient was a 41-year-old woman, who was not obese (exact BMI was not reported), had bilaterally decreased vision and a "left nasal hemianopia" with mildly dilated ventricles on MRI; in the second report, the patient was a 48-year-old man with normal neuroimaging whose BMI was not reported; in the third report, a 41-year-old man complained of distortion of peripheral vision and was found to have papilledema, and his OP on LP was normal, but because of the increased protein in CSF, he was eventually diagnosed with spinal cord plasmacytoma; in the fourth report, a morbidly obese 41-year-old woman experienced progressive visual loss, headaches, nausea, and vomiting and was found to have papilledema and anisocoria and was eventually diagnosed with intramedullary astrocytoma as a culprit producing elevated CSF protein (19)(20)(21)(22)(23). Another report highlighted a young man who presented with papilledema and was eventually diagnosed with carcinomatous meningitis due to adenocarcinoma of the lung; the patient was a very thin 30-year-old man (24). Two cases of spinal leptomeningeal lymphoma were reported that mimicked IIH: A 43-year-old woman, whose BMI was not reported had symptoms of headaches and dizziness for a year, was found to have papilledema and elevated CSF protein and eventually abnormal spinal MRI led to the diagnosis; the second case was that of a 49-year-old man, whose BMI was also not reported and who also had symptoms of increased ICP, was found to have papilledema while MRI of the brain was normal, and eventually, LP was performed demonstrating increased protein, and MRI of the spine led to the final diagnosis (25).…”
Section: Is Lumbar Puncture Necessary For the Diagnosis Of Idiopathic...mentioning
confidence: 99%
“…Several reports described spinal cord tumors misdiagnosed as IIH: In one, the patient was a 41-year-old woman, who was not obese (exact BMI was not reported), had bilaterally decreased vision and a "left nasal hemianopia" with mildly dilated ventricles on MRI; in the second report, the patient was a 48-year-old man with normal neuroimaging whose BMI was not reported; in the third report, a 41-year-old man complained of distortion of peripheral vision and was found to have papilledema, and his OP on LP was normal, but because of the increased protein in CSF, he was eventually diagnosed with spinal cord plasmacytoma; in the fourth report, a morbidly obese 41-year-old woman experienced progressive visual loss, headaches, nausea, and vomiting and was found to have papilledema and anisocoria and was eventually diagnosed with intramedullary astrocytoma as a culprit producing elevated CSF protein (19)(20)(21)(22)(23). Another report highlighted a young man who presented with papilledema and was eventually diagnosed with carcinomatous meningitis due to adenocarcinoma of the lung; the patient was a very thin 30-year-old man (24). Two cases of spinal leptomeningeal lymphoma were reported that mimicked IIH: A 43-year-old woman, whose BMI was not reported had symptoms of headaches and dizziness for a year, was found to have papilledema and elevated CSF protein and eventually abnormal spinal MRI led to the diagnosis; the second case was that of a 49-year-old man, whose BMI was also not reported and who also had symptoms of increased ICP, was found to have papilledema while MRI of the brain was normal, and eventually, LP was performed demonstrating increased protein, and MRI of the spine led to the final diagnosis (25).…”
Section: Is Lumbar Puncture Necessary For the Diagnosis Of Idiopathic...mentioning
confidence: 99%